ANALISIS RASIO KEUANGAN TERHADAP KINERJA KEUANGAN ALOKASI DANA DESA PEMERINTAHAN DESA BINAKA KECAMATAN GUNUNGSITOLI IDANOI KOTA GUNUNGSITOLI - Waruwu, Novi Ratna Suryani; Waruwu, Sukaaro; Bate'e, Maria Magdalena; Telaumbanua, Aferiaman; Halawa, Forman (Journal of Management Small and Medium Enterprises (SMEs), 2024)
The purpose of this study was to determine and analyze the financial performance of the Village Fund Allocation (ADD) management of Binaka Village Government, Gunungsitoli Idanoi District, Gunungsitoli City based on the ratio of effectiveness and growth ratio. The type of research used in this research is descriptive quantitative research. In this study, secondary data was obtained from the financial reports of Village Fund Allocations in the 2019-2021 APBDes Government of the Binaka Village. Data collection techniques used in this research are documentation and interviews. The results of the study show that the financial performance of the Allocation of Village Funds for the Government of Binaka Village from 2019-2021 based on the calculation of the effectiveness ratio with an average yield of 100% is categorized as effective. Then based on the growth ratio, it experienced negative growth with an average percentage of -5.4%. Keywords: Financial Performance; Effectiveness Ratio; Growth Ratio